1989
DOI: 10.1152/jappl.1989.66.3.1152
|View full text |Cite
|
Sign up to set email alerts
|

Blunted hypoxic ventilatory drive in subjects susceptible to high-altitude pulmonary edema

Abstract: It has been proposed that subjects susceptible to high-altitude pulmonary edema (HAPE) show exaggerated hypoxemia with relative hypoventilation during the early period of high-altitude exposure. Some previous studies suggest the relationship between the blunted hypoxic ventilatory response (HVR) and HAPE. To examine whether all the HAPE-susceptible subjects consistently show blunted HVR at low altitude, we evaluated the conventional pulmonary function test, hypoxic ventilatory response (HVR), and hypercapnic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 0 publications
3
40
1
Order By: Relevance
“…In addition, there may be confounding effects of sex and age. Since female subjects were not examined during the same phase of the menstrual cycle, and since there was a higher mean age than in previous studies [8,12,13], it is suggested that these potentially confounding factors [29][30][31] may account, in part, for the negative finding regarding the association between HVR and HAPE susceptibility. From a practical point of view, all those confounders are present in daily practice.…”
Section: Pulmonary Vascular Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there may be confounding effects of sex and age. Since female subjects were not examined during the same phase of the menstrual cycle, and since there was a higher mean age than in previous studies [8,12,13], it is suggested that these potentially confounding factors [29][30][31] may account, in part, for the negative finding regarding the association between HVR and HAPE susceptibility. From a practical point of view, all those confounders are present in daily practice.…”
Section: Pulmonary Vascular Responsementioning
confidence: 99%
“…Most studies report positive associations [8,12,13], although one study found no relationship between HAPE and HVR [14]. Furthermore, some studies have reported associations between susceptibility to HAPE and lower vital capacity [8,9,15,16] or lower functional residual capacity [16].…”
mentioning
confidence: 99%
“…1,2,18 The individual susceptibility has been suggested to be associated with enhanced pulmonary vascular responses to hypoxia, hypobaria, and exercise 26 or with blunted hypoxic ventilatory response. 27 Previously, measuring these physiological variables was a traditional means offering some indicators to the susceptibility. 26,27 Such tests, however, lacked sufficient reliability to gain widespread acceptance.…”
Section: Droma Et Al Polymorphisms Of Enos Gene In Hape 829mentioning
confidence: 99%
“…27 Previously, measuring these physiological variables was a traditional means offering some indicators to the susceptibility. 26,27 Such tests, however, lacked sufficient reliability to gain widespread acceptance. In this study, we used the novel missense variants of the eNOS gene to describe the association of the eNOS gene with HAPE for the first time.…”
Section: Droma Et Al Polymorphisms Of Enos Gene In Hape 829mentioning
confidence: 99%
“…34 In addition, less hypoxic peripheral chemoreceptor sensitivity may also directly affect the pulmonary vasculature via efferent communication from the brain, since for the same alveolar and arterial PO 2 those with lower HVR have greater HPV. 8 Subjects with lower HVR also have a much lower diuretic response to hypoxia, 35 which may lead to more pulmonary edema than in those that lose more salt and water in the initial several days at high altitude.…”
mentioning
confidence: 99%